1993
DOI: 10.1073/pnas.90.19.9159
|View full text |Cite
|
Sign up to set email alerts
|

Randomly amplified polymorphic DNA markers are superior to somatic incompatibility tests for discriminating genotypes in natural populations of the ectomycorrhizal fungus Suillus granulatus.

Abstract: Assessing genetic variation within populations and genetic exchange between populations requires an understanding of the distribution and abundance of individual genotypes within the population. Previous workers have used somatic incompatibility testing to distinguish dones or individuals in natural populations of ectomycorrhizal fungi. However, somatic incompatibility tests performed with isolates of Suilus granulatus from a natural population revealed a lack of transitiveness, which brought into question the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 16 publications
(17 reference statements)
3
61
0
Order By: Relevance
“…This means that S. bovinus genets may expand by mycelial growth. The same situations have also been found in S. granulatus populations (Jacobson et al, 1993) and S. pungens (Bonello et al, 1998). Similarly, genets of Laccaria bicolor have been observed to remain associated with same host for several years and extended their distribution by mycelial growth (de la Bastide et al, 1994 ;Selosse et al, 1998).…”
Section: mentioning
confidence: 60%
See 1 more Smart Citation
“…This means that S. bovinus genets may expand by mycelial growth. The same situations have also been found in S. granulatus populations (Jacobson et al, 1993) and S. pungens (Bonello et al, 1998). Similarly, genets of Laccaria bicolor have been observed to remain associated with same host for several years and extended their distribution by mycelial growth (de la Bastide et al, 1994 ;Selosse et al, 1998).…”
Section: mentioning
confidence: 60%
“…Studies of S. bovinus populations showed that genets were 1-30 m across (Dahlberg & Stenlid, 1990, 1994a, whereas the average genet size of S. variegatus was 20 m in old Scots pine stands and 10 m in young stands (Dahlberg, 1997). Similarly, genet sizes of S. granulatus (Jacobson et al, 1993) and S. pungens (Bonello et al, 1998) have been reported to be 20 m and 40 m, respectively. The above comparison also shows that S. grevillei genets seem to be rather smaller than those of other Suillus species.…”
Section: mentioning
confidence: 99%
“…The expression of somatic incompatibility reactions in S. collinitus iustihes its grouping with other Suillus species showing the same type of reaction (Fries, 1987;Sen, 1990a;Jacobson et al, 1993;Dahlberg & Stenlid, 1994). This suggests that it is heterothallic like other Suillus species (Fries & Neumann, 1990;Fries & Sun, 1992;Fries, 1994).…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, allozyme patterns have in some cases enabled identification of genets in fungi (Sen, 1990 ;Rodrigues et al, 1995 ;El Karkouri et al, 1996). The recent, rapid evolution of molecular techniques has facilitated the development of tools that can be applied to fungal populations : RFLPs (Egger et al, 1991 ;Egger, 1992 ;Smith et al, 1992 ;Bae et al, 1994 ;Matsumoto & Fukumasa-Nakai, 1995), randomly amplified polymorphic DNA (RAPDs) (Jacobson et al, 1993 ;de la Bastide et al, 1994 ;Liew & Irwin, 1994 ;Peever & Milgroom, 1994 ;Gosselin, Jobidon & Bernier, 1995 ;Raffle et al, 1995 ;Perotto et al, 1996) and amplified fragment length polymorphisms (AFLPs) (Mueller et al, 1996) have been reported to be useful and efficient in analysis of both spatial and temporal distribution and variation of genets in populations of fungi.…”
Section: A Jumpponenmentioning
confidence: 99%
“…These neutral loci might bear more variation within and among populations than functional gene products such as allozymes. Jacobson et al (1993) showed that somatically compatible isolates, which are frequently interpreted as representatives of a single genet, of Suillus granulatus (L. : Fr.) Kuntze might have distinct RAPD phenotypes.…”
Section: mentioning
confidence: 99%